Small bowel diverticulosis: imaging appearances, complications, and pitfalls. Issue 4 (April 2022) - Lamb, R.; Kahlon, A.; Sukumar, S.; Layton, B.
Abstract : Diverticula of the small bowel can be categorised as true, with Meckel's being the only example, or false. False small bowel diverticula (SBD) are acquired through herniation of the internal layers of the bowel wall through the muscularis propria. Peri-ampullary duodenal diverticula are a well-recognised example; however, the importance of more distal SBD in the jejunum and ileum is underappreciated, and they are under-reported on cross-sectional imaging. SBD are a known cause of anaemia, malabsorption, and diarrhoea, and there are myriad complications of SBD and Meckel's diverticula, which range in severity from inflammation and perforation to haemorrhage, tumour formation, and obstruction. Before the advent of computed tomography (CT), SBD were readily diagnosed on fluoroscopic oral contrast studies; however, radiologists are less comfortable with their cross-sectional imaging appearances. This imaging review combines our experience of multiple proven cases, with illustrative diagrams and radiological images of SBD to provide distinct imaging characteristics, allowing for confident diagnosis of SBD and their numerous complications. We discuss the importance of SBD as a cause of benign, non-surgical pneumoperitoneum. We additionally provide important pitfalls to be aware of such as SBD masquerading as other abnormalities.